Gaya Kepemimpinan Situasional Kepala Sekolah Alam Lukulo Kebumen - Muna Fauziah; Sulis Rokhmawanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Insitut Agama Islam Nahdlatul Ulama (IAINU) Kebumen, 2020)
This study intends to analyze the situational leadership style of the principal to improve the quality of education at the Lukulo Natural School, Kebumen. The research was carried out at the Lukulo Nature School, Kebumen. The participant of this research is the principal of the Lukulo Natural School, Kebumen. The author uses descriptive qualitative research methods. Data were collected through observation, interviews, and documentation. All data were analyzed using an interactive model with the flow: data recording, data presentation, and drawing conclusions. The research found that the principal of the Alam Lukulo Kebumen School applied several leadership styles to improve the quality of education at the Lukulo Kebumen Nature School in the form of telling style (giving work to subordinates and directing), selling style (making clear rules), participating style (solving problems together) , and delegating style (giving full responsibility to the teacher).